A new flesh fly species of Oxysarcodexia Townsend from the Brazilian Atlantic Forest and redescription of Oxysarcodexia xon (Dodge, 1968) - Menezes, Marco Antônio; Santos, Josenilson Rodrigues dos; Mello-Patiu, Cátia Antunes de (Papéis Avulsos de Zoologia, 2020)
A new Neotropical species of Oxysarcodexia Townsend (Diptera, Sarcophagidae) from Atlantic Forest of southeastern Brazil, Oxysarcodexia digitata sp. nov., is described and illustrated based on male and female specimens. This new species resembles O. fraterna Lopes, O. nitida Soares & Mello-Patiu, O. notata Soares & Mello-Patiu, O. vittata (Walker), and O. xon (Dodge), but can be distinguished based on differences in phallic elements. Additionally, the male of Oxysarcodexia xon (Dodge, 1968) is redescribed and illustrated, its female is described for the first time, and new records is presented.